2011
DOI: 10.1007/s10804-010-9117-4
|View full text |Cite
|
Sign up to set email alerts
|

Music and Stress

Abstract: Myths about the power of music to regulate and change emotional states are found in each culture. Googling the words ''music and stress'' produces promises for different types of music specially designed to assist managing stress. Music therapists are familiar with using different techniques to reduce stress with different populations. This paper examines both the application of music to stress management and the neurological and physiological mechanisms of stress that can be modulated by music.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 63 publications
4
46
0
1
Order By: Relevance
“…Greater collaboration between the fields of music therapy and music neuroscience may accelerate the pursuit of these objectives. Finally, given the emerging evidence that earlier involvement of palliative care may improve outcomes in certain cancer patients [129], and that psychological stress may be linked to up-regulation of inflammatory processes that promote tumor growth and angiogenesis [130133], it follows that research into the potential of music to specifically promote relaxation and reduce stress [134], perhaps earlier in cancer’s trajectory, may also be warranted.…”
Section: Resultsmentioning
confidence: 99%
“…Greater collaboration between the fields of music therapy and music neuroscience may accelerate the pursuit of these objectives. Finally, given the emerging evidence that earlier involvement of palliative care may improve outcomes in certain cancer patients [129], and that psychological stress may be linked to up-regulation of inflammatory processes that promote tumor growth and angiogenesis [130133], it follows that research into the potential of music to specifically promote relaxation and reduce stress [134], perhaps earlier in cancer’s trajectory, may also be warranted.…”
Section: Resultsmentioning
confidence: 99%
“…Pythagoras (580/500 BCE) prescribed musical intervals to promote health; And Aristotle (384/322 BC) defended music as an emotional catharsis [28,29]. Music helps in stress reduction, cardiac function, relaxation, pain management, among others and has been used in several scenarios as a complementary therapy [30,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, It can be observed that Piano, no chords (melody), and the musical scale G Major Pentatonic are the symbolic data with the highest number of evaluations when listeners felt astonished. (7) 0.125(10), 0.15 (2) 0.063(9) Relaxed 0.885 (2) 0.501 (13) 0.367 (13) 0.158 (22) 0.063 (7) At ease 0.97 (6) 0.487 (15) 0.311 (7) 0.13 (29) 0.064(12) Tired 0.77(7), 0.906 (12) 0.49 (14) 0.337 (14) 0.132(15) -Droopy 1 (2) 0.4(3), 0.53 (7) 0.34(4) 0.16(28) -Depressed 1 (5) 0.52 (14) 0.37 (18) …”
Section: Discussionmentioning
confidence: 99%
“…Yehuda [29] examines the application of music to stress management, as well as the neurological and physiological mechanisms of stress that can be modulated by music.…”
Section: Emotional Effects Of (Known) Musical Piecesmentioning
confidence: 99%